Вплив освіти, ЗМІ, групи рівних (peer groups) та громадських рухів на політико-ідеологічну ідентифікацію молоді - Агаларова, Карина Адільївна (Національний технічний університет "Харківський політехнічний інститут", 2016)
Стаття присвячена вивченню впливу таких об’єктивних та суб'єктивних чинників політико-ідеологічної ідентифікації молоді як освіті, засобам масової інформації та групам рівних (peer groups), громадським рухам, асоціаціям. У статті доведено значна роль яку відіграють ці чинники у формуванні суб'єктних характеристик молоді, а також їх суперечливий вплив у формуванні політико-ідеологічної ідентифікації молоді. Автором зроблено висновок про те, що значний вплив на формування політичних цінностей молоді здійснюють групи рівних (peer groups), громадські рухи, асоціації. Проаналізовані чинники політико-ідеологічної ідентифікації особистості виокремленні відповідно до ступені впливу на зазначений процес, проте всі вони взаємопов’язані, і саме кумулятивний ефект їхнього впливу сприяє формуванню усталеної політико-ідеологічної ідентичності особистості. На підставі аналізу впливу освіти та ЗМІ на політикоідеологічну ідентифікацію, автор приходе до висновку про те, що відсутність у студентської молоді політичних знань може привести до перетворення її на об'єкт маніпуляцій різноманітних політичних сил.

This article is devoted to the study of influence of objective and subjective factors of political and ideological identification of youth education, media and peer groups, social movements, associations. The relevance of the topic chosen is because students today feel the controversial impact of the various institutions of political socialization, including education and the media, which in turn determines the contradictory political development of this social group, a political and ideological identities. Also, a great influence is on the formation of political values youth peer groups, social movements, associations. Investigated factors in article political and ideological identification differ in their impact on this process, but they are all interrelated, and that the cumulative effect of their influence contributes to a well-established political and ideological identity cards. The paper proved the significant role played by these factors in the formation of subjective characteristics of young people and their contradictory influence in shaping the political and ideological identification of young people. The analysis of the impact of education and the media on political and ideological identification of young people had been providing that lack of political knowledge of students can cause that it becomes an object of manipulation of various political forces, what important role can play a growing role of the media and internet as agents of political socialization. In article describe the influence on the formation of political values young man peer groups, interest groups, associations, youth movements and others. They offer samples of political behavior for its members and trying to fix specific and political orientation, and in terms of Ukraine becoming increasingly noticeable tendency creation of youth organizations (sections, sectors, groups) political parties.
The impact of education, the mass media, peer groups and social movements in the political and ideological identification of youth
Keywords: політико-ідеологічна ідентичність; політична соціалізація; політична суб'єктність; маніпуляції; political and ideological identity; political socialization; political subjectivity